Edukasi Strategi Pemasaran Sukses Usaha UMKM di Era Digital - Brandinie, Morryessa; Apriwenni, Prima (Jurnal Abdimas: Sosial, Bisnis, dan Lingkungan, 2024)
The Covid-19 pandemic has had a major impact on the government and society. Many business actors experienced a decline in sales turnover. This pandemic requires MSME owners to be able to think strategically and dynamically to maintain the businesses they have built. Many MSMEs today are still experiencing difficulties in advancing their businesses. And now business people, to find ideas, carry out administration, market products or services as well as recording and reporting activities, have to utilize effective marketing strategies and must take advantage of digital technology which is increasingly developing at this time. Several marketing strategies can be used to overcome the problems that occur. One thing that is considered very effective in the field of marketing today is adopting various digital media and technologies.